2021
DOI: 10.3390/ijerph18178942
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions and Urinalysis Dipstick Testing among Female Rice Farmers: A Preliminary Cross-Sectional Study

Abstract: This cross-sectional study aimed to assess working conditions and renal function among female rice farmers in Nan Province, Thailand. Purposive random sampling was used to select participants who met the inclusion criteria. Data were collected from 65 female rice farmers using in-depth interviews. A walk-through survey was performed to examine hazards in the rice farm and a dipstick test was used for urinalysis. The results demonstrated that all rice farming stages contained risks from physical, chemical, biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We found that frequent pest management and inadequate work breaks were risk factors for STFs. The result regarding pest management can be explained by the work characteristics of this type of farm operation 18 ) . Pest management is performed intermittently between planting and harvest to protect corn from insects, weeds, and diseases 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…We found that frequent pest management and inadequate work breaks were risk factors for STFs. The result regarding pest management can be explained by the work characteristics of this type of farm operation 18 ) . Pest management is performed intermittently between planting and harvest to protect corn from insects, weeds, and diseases 19 ) .…”
Section: Discussionmentioning
confidence: 99%